(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: This study delves into the intricate nexus between indigenous knowledge, entrepreneurship, and socio-economic development, focusing on the context of Gujarat, India. Indigenous knowledge, deeply rooted in the cultural fabric of indigenous communities, encompasses traditional practices, skills, and wisdom passed down through generations. Using indigenous knowledge to promote sustainable development, indigenous entrepreneurship has been a powerful driver for socioeconomic reform in recent years. Gujarat is a great place to study the dynamics of indigenous entrepreneurship because of its thriving business environment and rich cultural history. Using their local knowledge to create jobs, add value, and promote inclusive growth, indigenous entrepreneurs in Gujarat are pursuing a range of business ventures, from eco-tourism to agro-based industries. This study employs a multi- disciplinary approach, drawing on insights from anthropology, economics, and entrepreneurship studies to explore the interplay between indigenous knowledge, entrepreneurial endeavors, and socio-economic outcomes in Gujarat. By analyzing case of Mitticool Private Limited, this study illuminates the diverse ways in which indigenous knowledge informs entrepreneurial activities in Gujarat. Additionally, this research looks at the socioeconomic effects of indigenous entrepreneurship in Gujarat, analysing how it contributes to the reduction of poverty, the preservation of culture, and the empowerment of local communities. Indigenous entrepreneurs provide economic possibilities and promote social cohesion at the same time as they preserve indigenous knowledge systems through creative business structures.